Student’s Perception of the Development of Short Distance Running Learning through Traditional Games - Nurjaliansyah, Nurjaliansyah; Lanos, Muhsana El Cintami; Handayani, Widya (Journal of Social Work and Science Education, 2023)
This study aims to determine students’ perceptions of short-distance running learning models through traditional games based on (1) Perceptions of knowledge of learning short-distance running, (2) Perceptions of teachers’ teaching styles, (3) Perceptions of the media used, (4) Perceptions of interest in learning short-distance running, (5) Perceptions of the need to develop short-distance running learning models through traditional games. This research is descriptive quantitative research. The results of this study showed that (1) Perception of knowledge of learning to run short distances obtained a score of 93.50% in the very good category, (2) Perception of teacher teaching style obtained a score of 78.50% in the good category, (3) Perception of the media used was easy to use obtained a score of 88% in the very good category, (4) Perception of interest in learning physical education obtained a value of 96.30% in the very good category, (5) The perception of the need to develop a learning model of basic volleyball techniques through a playing approach obtained a score of 100% in the very good category, which means that students agree if the development of a learning model of short-distance running through traditional games is developed. The results of this study show that students’ perceptions of the development of short-distance running learning models through traditional games in elementary schools in North Musi Rawas Regency are positive, for that it is necessary to develop short-distance running learning models through traditional games.